The Acadian plutonic rocks of New Brunswick - Fyffe, L. R.; Pajari, G. E.; Cherry, M. E. (Atlantic Geoscience, 1981)
Extensive bimodal plutonism accompanied and followed the Acadian deformation in New Brunswick. These Acadian plutons define a Central Plutonic Belt, which is largely confined to a terrain with an Acadian trend of 030*, and a Southern Plutonic Belt, which occurs within a structural province with an Acadian and Varlscan trend of 060". It has been possible to classify the Acadian plutons north of the Avalonian Platform according to their structures, textures, field relationships, mineralogy, and chemical characteristics; supplemented by radiometric age dates. Plutonic rock types include: A-B a mafic-felalc association; C - syntectonic conalite and granodiorite; D - suscovlte-bearing; F - megacrystic granitoids; H - equigranular biotite granites; and E and G - ’transitional’ granites. The magmatism, regardless of location, follows a common evolutionary trend and appears to comprise a sequence of intrusions from early Devonian to Carboniferous time with no significant break in the evolution. These characteristics along with the bimodal chemistry and the lack of compositional polarity suggest that the development of these Acadian plutons was not subduction-related. A time-dependent process such as radioactive heating of a thickened crust is a more probable mechanism for their genesis. RÉSUMÉ Au Nouveau-Brunswick, la déformation acadienne fut accompagnée puis suivie d’un plutoniame bimodal très étendu. Ces plutons acadiens définissent une zone intrusive centrale et une zone intrusive méridional: la première se confine en grande partie dans une région qui présente une orientation acadienne de 030* alors que la seconde se trouve à l’intérieur d’une province structurale marquée par une orientation acadienne et variaque de 060*. Au nord de la plate-forme avalonienne, les plutons acadiens ont pu être classifiés selon leurs structures, textures, relations de terrain ainsi que leurs caractérisques minéraloglques et chimiques, le tout étant complété par des datations radiométriques. Les roches intrusives comprennent: A-B une association mafique et felsique; C - une granodiorite et une tonalite syntectoniques; D - roches intrusives à muacovite; F - granitoides à biotite équigranulaire; et E et G - granites "de transition". Peu importe l’endrolt, on observe une tendance évolutive commune à ce magmatlsme qui semble comprendre une suite d’intrusions, évoluant sans interruption du Dévonien inférieur au Carbonifère. Ces caractérlstlques, en plus de Is bimodalité du chimisme et de l’absence de polarité de composition, suggèrent que ces plutons acadeins ne furent pas formés par subduction. Pour engendrer ceux-ci, un processus lié au temps, tel que le réchauffement radioactif d’une croûte qui s’est épaissie, est plus probable. [Traduit par le Journal]